Asymptomatic postoperative deep vein thrombosis and the development of postthrombotic syndrome - Wille-Jørgensen, Peer; Jorgensen, Lars N.; Crawford, Michael (Thrombosis and Haemostasis, 2005)
Perioperative antithrombotic clinical regimens have reduced the incidence of postoperative deep venous thrombosis (DVT). Long-term effects of asymptomatic postoperative DVT have been studied in a number of clinical trials and the present review describes the clinical significance of asymptomatic postoperative DVT regarding the possible development of postthrombotic syndrome (PTS).We performed a systematic review of reference databases focusing upon studies including patients suspected of having postoperative DVT and reporting subsequent cases of PTS at the end of a well-defined follow-up period. The included studies were stratified according to type of screening method and applied statistics. Over-all evaluation included metaanalyses based upon the Cochrane software package. The overall relative risk of developing PTS was 1.58 (95% confidence intervals: 1.24 – 2.02) in patients suffering from asymptomatic DVT as compared to patients without DVT ( p < 0.0005).In conclusion, asymptomatic postoperative DVT is associated with an increased risk of late development of PTS. The finding emphasizes that postoperative DVT, diagnosed by means of well-defined objective measures, remains the correct scientific endpoint in trials evaluating the efficacy of preoperative antithrombotic treatment regimens.
Keywords: Postthrombotic syndrome; deep vein thrombosis; surgery